English Teaching Materials With Flipped Learning Model in English Course - Febriati, Farida; Jaya, Dirwan; H, Nurhikmah; Sujarwo (Universitas Pendidikan Ganesha, 2022)
The success or failure of a lesson will be seen during the teaching and learning process because it will show how prepared the learner is with the suitable materials and strategies. This study aims to analyze the need for developing teaching materials, designing teaching materials, and validating the validity and practicality of the effectiveness of developing teaching materials in English courses. This research method is Research and Development. The development model refers to S. Thiagarajan et al., which consists of 4 stages: Define, design, develop, and Disseminate. The research subjects were 38 students and one lecturer. Data collection techniques using qualitative and quantitative methods (interviews, observations, documentation, and questionnaires). English teaching materials were developed and validated by material and media experts, with material and media validation being very valid. The small group trials obtained a very practical category. In contrast, the large group trials obtained a practical category and, as seen from the lecturer's response in assessing teaching materials, obtained a very practical category. Meanwhile, the effectiveness of teaching materials can be seen from the passing rate on tests given to students, with results > 80 in the very good category. Based on the results found, it can be concluded that practical and effective teaching materials are used in the learning process in English courses.